At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Certainly! Let's break down the steps to solve the inequality [tex]\(\frac{3}{x+2} + 4 \geq 3\)[/tex] and explain why the solution does not include [tex]\(x = -2\)[/tex].
### Step-by-Step Solution:
1. Subtract 4 from both sides:
[tex]\[\frac{3}{x+2} + 4 - 4 \geq 3 - 4\][/tex]
Simplifying this expression, we get:
[tex]\[\frac{3}{x+2} \geq -1\][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]:
To do this, let's consider the inequality:
[tex]\[ \frac{3}{x+2} \geq -1 \][/tex]
We need to remove the denominator on the left side. We'll multiply both sides of the inequality by [tex]\(x+2\)[/tex], but we must be careful: the sign of [tex]\(x+2\)[/tex] could be positive or negative, which affects our inequality direction.
[tex]\[ \begin{cases} \frac{3}{x+2} \cdot (x+2) \geq -1 \cdot (x+2) & \text{if } x \neq -2 \end{cases} \][/tex]
3. Simplify and solve for [tex]\(x\)[/tex]:
The term [tex]\(\frac{3}{x+2} \cdot (x+2)\)[/tex] simplifies to 3, providing:
[tex]\[ 3 \geq -1(x + 2) \][/tex]
Distribute [tex]\(-1\)[/tex] on the right side:
[tex]\[ 3 \geq -x - 2 \][/tex]
Add 2 to both sides to simplify:
[tex]\[ 3 + 2 \geq -x \][/tex]
[tex]\[ 5 \geq -x \][/tex]
Multiply both sides by [tex]\(-1\)[/tex] (remember to reverse the inequality sign):
[tex]\[ -5 \leq x \][/tex]
Or,
[tex]\[ x \geq -5 \][/tex]
4. Consider [tex]\(x = -2\)[/tex]:
Throughout these steps, an important factor is that [tex]\(x \neq -2\)[/tex] because if [tex]\(x = -2\)[/tex], the denominator in the original inequality [tex]\(\frac{3}{x+2} + 4 \geq 3\)[/tex] would become zero, which would make the fraction undefined.
[tex]\[ \frac{3}{x + 2} \quad \text{is undefined when } x = -2 \][/tex]
### Conclusion:
The solution to the inequality [tex]\(\frac{3}{x+2} + 4 \geq 3\)[/tex] is [tex]\(x \geq -5\)[/tex], but not including [tex]\(x = -2\)[/tex], because at [tex]\(x = -2\)[/tex] the term [tex]\(\frac{3}{x+2}\)[/tex] is undefined (it involves division by zero).
Thus, the range of [tex]\(x\)[/tex] is:
[tex]\[ x \in [-5, \infty) \quad \text{excluding} \quad x = -2 \][/tex]
This exclusion of [tex]\(x = -2\)[/tex] is why there is an open circle at [tex]\(x = -2\)[/tex] on the graph of the solution. An open circle represents a value that is not included in the solution set.
### Step-by-Step Solution:
1. Subtract 4 from both sides:
[tex]\[\frac{3}{x+2} + 4 - 4 \geq 3 - 4\][/tex]
Simplifying this expression, we get:
[tex]\[\frac{3}{x+2} \geq -1\][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]:
To do this, let's consider the inequality:
[tex]\[ \frac{3}{x+2} \geq -1 \][/tex]
We need to remove the denominator on the left side. We'll multiply both sides of the inequality by [tex]\(x+2\)[/tex], but we must be careful: the sign of [tex]\(x+2\)[/tex] could be positive or negative, which affects our inequality direction.
[tex]\[ \begin{cases} \frac{3}{x+2} \cdot (x+2) \geq -1 \cdot (x+2) & \text{if } x \neq -2 \end{cases} \][/tex]
3. Simplify and solve for [tex]\(x\)[/tex]:
The term [tex]\(\frac{3}{x+2} \cdot (x+2)\)[/tex] simplifies to 3, providing:
[tex]\[ 3 \geq -1(x + 2) \][/tex]
Distribute [tex]\(-1\)[/tex] on the right side:
[tex]\[ 3 \geq -x - 2 \][/tex]
Add 2 to both sides to simplify:
[tex]\[ 3 + 2 \geq -x \][/tex]
[tex]\[ 5 \geq -x \][/tex]
Multiply both sides by [tex]\(-1\)[/tex] (remember to reverse the inequality sign):
[tex]\[ -5 \leq x \][/tex]
Or,
[tex]\[ x \geq -5 \][/tex]
4. Consider [tex]\(x = -2\)[/tex]:
Throughout these steps, an important factor is that [tex]\(x \neq -2\)[/tex] because if [tex]\(x = -2\)[/tex], the denominator in the original inequality [tex]\(\frac{3}{x+2} + 4 \geq 3\)[/tex] would become zero, which would make the fraction undefined.
[tex]\[ \frac{3}{x + 2} \quad \text{is undefined when } x = -2 \][/tex]
### Conclusion:
The solution to the inequality [tex]\(\frac{3}{x+2} + 4 \geq 3\)[/tex] is [tex]\(x \geq -5\)[/tex], but not including [tex]\(x = -2\)[/tex], because at [tex]\(x = -2\)[/tex] the term [tex]\(\frac{3}{x+2}\)[/tex] is undefined (it involves division by zero).
Thus, the range of [tex]\(x\)[/tex] is:
[tex]\[ x \in [-5, \infty) \quad \text{excluding} \quad x = -2 \][/tex]
This exclusion of [tex]\(x = -2\)[/tex] is why there is an open circle at [tex]\(x = -2\)[/tex] on the graph of the solution. An open circle represents a value that is not included in the solution set.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.